Fiscal Policy over the Election Cycle in Low-Income Countries - Ebeke, Christian (IMF Working Papers; Working Paper, 2013)
Focusing on Low-Income Countries, we investigate the behavior of fiscal variables during and after elections. The results indicate that during election years, government consumption significantly increases and leads to higher fiscal deficits. During the two years following elections, the fiscal adjustment takes the form of increased revenue mobilization in trade taxes and cuts to government investment, with no significant cuts in government consumption. Using a new dataset on national fiscal rules and IMF programs, we find that both the presence of fiscal rules and IMF programs help dampen the magnitude of the political budget cycle in LICs. We conclude that elections not only imply a macroeconomic cost when they take place but also trigger a painful fiscal adjustment in which public investment is largely sacrificed.